PERUBAHAN FISIK DAN CITA RASA KOPI ARABIKA AKIBAT LEVEL ROASTING SECARA FULL WASH - purnama, rizsky wan (Universitas Gajah Putih, 2024)
Abstract. Arabica coffee is one of the drinks that has a delicious taste and distinctive aroma and has a positive effect on health. Furthermore, Arabica coffee is very popular with local people and the world community. The coffee roasting process has a crucial role in forming the characteristics of the taste and aroma of the coffee produced. The coffee roasting process is divided into light roasting temperatures, namely 190 ° C - 195 ° C and medium roasting temperatures of 200 ° C - 205 ° C, which greatly determines the taste to be enjoyed and is very important for the coffee processing stages. Arabica coffee in Central Aceh has great potential, but has not been identified based on the roasting level. A deep understanding of the effect of roasting levels on Arabica coffee brewing is important to meet the increasing consumer needs for high-quality coffee. Although there has been a lot of research on the coffee roasting process, there is still a need to better understand how roasting levels affect the characteristics of coffee brewing, especially Arabica coffee, especially in Central Aceh. The data sources used in this study are primary and secondary data. Primary data was obtained directly from the original source through a questionnaire, this data was obtained from the panelists' responses to the assessment of coffee samples for taste testing. In other words, researchers collect data by answering research questions through a survey method, the data is then recorded in a sensory assessment form. In this study, the data was analyzed quantitatively using analysis of variance (ANOVA) by looking at the calculated F value to determine the differences between sample groups. The results of the panelists' assessment of all samples of light roast, medium roast and dark roast roast levels were significant differences, color, coffee aroma, coffee taste, bitter taste, sweet taste, sour taste, thickness/body, and overall acceptance while for appearance and aftertaste there was no significant difference